Children Education in the Brazilian scenario after parliamentary coup: Public policy and evaluation - Ângela Scalabrin Coutinho; Catarina Moro (Universidade Federal de Santa Catarina, 2017)
This article aims to analyze the changes in the public police propositions of Children Education, in particular the evaluation policies concerning this stage, due to the change of government resulting from the parliamentary coup that had its end in the first half of 2016. Therefore, it sets the recent course of elaborating an evaluation policy for this educational stage, highlighting the goals and strategies of Plano Nacional de Educação (PNE) and links it to other ongoing policies, such as the curriculum, which currently has as its main scope the definition of a Base Nacional Comum Curricular (BNCC). It is identified that the revocation of the decree that defined the Sistema Nacional de Avaliação da Educação Infantil (ANEI) and the presentation of a third version of BNCC, focused on a curricular perspective based on skills and abilities and with an emphasis on writing in children's education, jeopardizes the process of defining a descentralized evaluation policy on the individual performance of children and is concerned about the quality of education provision. Another aspect of attention is the aliances estabilished in the definition of educational policies, in order to identify the participation of private entities not only in the implementation of policie but in their formulation, which reveals a clear choice for privatist logic of government.